Highly efficient exchange of orbital angular momentum of light via electron spin coherence. (1st January 2023) - Alkawak, Omar A; Faisal Raheem, Al-Behadili; Yasin, Yaser; Ibrahim, Wessim Salahaddin; Ruhaima, Ali Abdul Kadhim; Hassan Ward, Zahraa; Hadrawi, Salema K; Kong, H
Abstract: In this letter we analysed the efficient exchange of orbital angular momentum (OAM) of light in a double V-type semiconductor quantum well via electron spin coherence. We found that due to the four-wave mixing (FWM) mechanism the OAM state of the vortex light can transfer from applied lights to a new generated signal beam when the efficiency of the FWM processes is enough high. We also shown that the absorption spectrum of the new generated light depends on the OAM number and azimuthal angle of the optical vortex light. We realized that for some specific parametric conditions the absorption spectrum of the generated light becomes negative which corresponds to the lasing without inversion.